Валидность интуиционизма в создании искусственного интеллекта - Киряк, А. А. (ХНУРЕ, 2019)
This paper explores the use of intuitionism to create artificial intelligence. Intuition is considered as a method of scientific knowledge. The problem of “modeling” intuition in artificial intelligence is also considered. An explanation of the concept of "Intuition", "artificial intelligence." Intuitionism is revealed as a way to obtain mathematical results using intuition.